Politik Hukum Dispensasi Kawin: Membatasi Perkawinan Anak melalui Politik Batas Usia - Ashabul Fadhli; Rahmiati Rahmiati; Fathur Rahmi; Jelang Ramadhan (Institut Agama Islam Negeri Kerinci, 2022)
This study aims to find out the dialectic of formulating the age limit for marriage which took place from the pre-independence period until the issuance of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Applications for Marriage Dispensation. The demand to determine the age limit was first voiced by the women's movement explicitly during the colonial period due to the large number of daughters being married off. Child marriage has been detrimental and has a bad impact on the lives of girls. This research is a normative legal research that uses a statutory approach, a conceptual approach and a historical (historical) approach. The results of this study prove that the formulation of the politically negotiated age limit after the independence period did not receive special attention by the Government. Interests in other matters concerning the approval of the Marriage Law are generally more important. The issue of the age limit has received a lot of criticism after Article 7 of Law No. 1/1974 on marriage was judged to be casuistic in terms of legal material and judicial practice. With the promulgation of PERMA Number 5 of 2019 it becomes the determinant of the legal vacuum regarding the application of the age limit rule and the process of adjudicating marriage dispensation cases by judges in the Religious Courts.